2021
DOI: 10.1097/mpg.0000000000003218
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications in Pediatric Pancreatitis: A Case Series

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Some authors argue that these thromboses occur as part of the inflammatory process during an episode of pancreatitis, and the thromboses will spontaneously recanalize when the acute inflammation has resolved. They report similar recanalization rates in their patients who had pancreatitis-associated splanchnic venous thrombosis treated with anticoagulants and those who did not have anticoagulant intervention [ 2 , 4 , 5 , 7 , 13 ]. Additionally, a recent meta-analysis concluded that there is no evidence to encourage routine use of anticoagulants in patients with splanchnic venous thrombosis associated with pancreatitis and that prospective studies are needed [ 13 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Some authors argue that these thromboses occur as part of the inflammatory process during an episode of pancreatitis, and the thromboses will spontaneously recanalize when the acute inflammation has resolved. They report similar recanalization rates in their patients who had pancreatitis-associated splanchnic venous thrombosis treated with anticoagulants and those who did not have anticoagulant intervention [ 2 , 4 , 5 , 7 , 13 ]. Additionally, a recent meta-analysis concluded that there is no evidence to encourage routine use of anticoagulants in patients with splanchnic venous thrombosis associated with pancreatitis and that prospective studies are needed [ 13 ].…”
Section: Discussionmentioning
confidence: 88%
“…We report 2 cases of children with pancreatitis-associated splenic vein thrombosis occurring during moderately severe to severe AP attacks that were successfully managed with oral anticoagulants. Splanchnic vein thrombosis is a known but unusual complication of pancreatitis in children, with a reported incidence of only 1.2% in the INSPPIRE cohort [ 7 ]. The splenic vein is the most common vein involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular complications of acute pancreatitis (AP) include pseudoaneurysm-induced hemorrhage, ischemic complications, and hypercoagulability-induced venous thrombosis [ 1 ]. In pediatric AP, these complications are rare, and treatment experience is limited [ 2 ]. Although there are several reports of endovascular embolization for pseudoaneurysms or anticoagulation for venous thrombosis, evidence for the role of total pancreatectomy (TP) to control these complications has been rarely discussed.…”
Section: Introductionmentioning
confidence: 99%